2011
DOI: 10.4049/jimmunol.1002213
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Selectively Inhibits Respiratory Burst Activity and Killing of Staphylococcus aureus in Human Neutrophils

Abstract: Neutrophils play a central role in the innate immune response and a critical role in bacterial killing. Most studies of neutrophil function have been conducted under conditions of ambient oxygen, but inflamed sites where neutrophils operate may be extremely hypoxic. Previous studies indicate that neutrophils sense and respond to hypoxia via the ubiquitous prolyl hydroxylase/hypoxia-inducible factor pathway and that this can signal for enhanced survival. In the current study, human neutrophils were shown to upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(138 citation statements)
references
References 53 publications
9
127
2
Order By: Relevance
“…Studies of neutrophils isolated from human volunteers or mice exposed to hypoxia have shown an increase in ROS production [44,56,65], although, of note, all cell isolation and in vitro assays were conducted under normoxic conditions. Whilst HIF-1a manipulation did not affect ROS release [55,60], in vitro assays conducted under hypoxia have consistently shown decreased intracellular and extracellular superoxide anion production, restored by re-oxygenation [54] and further increased under hyperbaric oxygen conditions. Moreover, intermittent hypoxia and its clinical correlate obstructive sleep apnoea appear to prime neutrophils for augmented superoxide anion generation [68].…”
Section: Reactive Oxygen/nitrogen Speciesmentioning
confidence: 92%
See 4 more Smart Citations
“…Studies of neutrophils isolated from human volunteers or mice exposed to hypoxia have shown an increase in ROS production [44,56,65], although, of note, all cell isolation and in vitro assays were conducted under normoxic conditions. Whilst HIF-1a manipulation did not affect ROS release [55,60], in vitro assays conducted under hypoxia have consistently shown decreased intracellular and extracellular superoxide anion production, restored by re-oxygenation [54] and further increased under hyperbaric oxygen conditions. Moreover, intermittent hypoxia and its clinical correlate obstructive sleep apnoea appear to prime neutrophils for augmented superoxide anion generation [68].…”
Section: Reactive Oxygen/nitrogen Speciesmentioning
confidence: 92%
“…Extravasated neutrophils undergo shape change to a polarised morphology, which is essential for directional movement. McGovern et al showed no change in IL-8-induced shape change, or chemotaxis towards IL-8, bacterial formylated peptide (fMLF) or LPS in human neutrophils cultured under hypoxia [54], and, likewise, Peyssonnaux et al found no difference in chemotaxis towards fMLF through an endothelial monolayer between wildtype, HIF-1a null and vHL-null murine neutrophils [55]. In contrast, Wang and Liu showed enhanced chemotaxis of neutrophils isolated from hypoxic subjects [56], whereas Rotstein et al showed reduced chemotaxis of human neutrophils towards fMLF and zymosan-activated serum under hypoxia in an agarose gel migration assay [57].…”
Section: Adhesion Transmigration Chemotaxis and Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations